Digital learning for old(er) workers : a systematic review of age-appropriate vocational education and training - Staniczek, Selina [Verfasser]; Naegele, Laura [Verfasser]; Schmitz, Wiebke [Verfasser] (My University, 2026)
"Demographic change and digitalization are reshaping both the workforce and the nature of work itself, highlighting the need for age-appropriate continuing vocational education and training (CVET). This systematic review examines the current state of research on digital CVET tailored specifically for old(er) workers. Guided by an adapted framework based on Lewin’s Change Theory (1947), we conceptualized digital learning as a three-phase process and aligned our research questions with each phase: RQ1 (prelude) explores factors influencing motivation and attitude shifts; RQ2 (engagement) examines the adoption of new learning behaviors and necessary adjustments in delivery; and RQ3 (sustain) investigates strategies to support long-term knowledge retention. We systematically searched four databases and one search engine (ERIC, GeroLit, PubMed, FIS Bildung, Google Scholar), identifying 40 relevant publications/studies (2001–2023). Inclusion criteria were: (i) publications in English or German; (ii) journal articles, book chapters, reports, or conference papers; (iii) investigation of digital learning measures; (iv) employed learners aged 40 or older; (v) job-related training; and (vi) detailed descriptions of learning elements. Dual-independent screening ensured rigor. Findings reveal a fragmented evidence base with inconsistent terminology, but highlight key factors shaping digital CVET experiences across all phases: stereotypes, self-efficacy, motivation, prior experiences, organizational support, learning format, and historical/cultural context. Practical implications include designing flexible, tailored learning environments, providing continuous practice and feedback, and fostering organizational conditions that reduce stereotypes and other barriers to participation. Future research should prioritize representative samples, longitudinal methods, and cross-cultural and sectoral perspectives to better meet the learning preferences of old(er) workers." (author's abstract ; BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; P 1.8 Ältere; L 4.2.3 Internetbasiertes Lernen / E-Learning; G 2.2.1 Technologisierung; 370; 300; Berufliche Weiterbildung; Älterer Arbeitnehmer; E-Learning; Digitalisierung; Weiterbildungsmotivation; Weiterbildungsbereitschaft; Lernverhalten; Lerntransfer